A cross sectional study to assess psychological impact of COVID-19 on health care workers in KIMS Bangalore - Ramya, H. S.; ., Keerthidarshini; L., Sanjay; Asiya, Afroza (International Journal of Contemporary Pediatrics, 2021)
Background: The ongoing coronavirus disease-2019 (COVID-19) pandemic has resulted in substantial psychological stress and anxiety for healthcare workers, we did a study targeting the healthcare workers to assess the magnitude of stress and anxiety in tertiary care centre. Methods: We conducted a cross sectional survey-based study among 150 healthcare workers working at KIMS hospital, Bangalore from September 2020 to December 2020. Stress and anxiety were investigated using DASS-21 scale, association of stress and anxiety with demographic factors such as age, sex, profession, living with family/alone, past history and family history of any psychiatric illness were analysed using chi-square test. Results: In 150 participants who were included in the study, 47 were males and 103 were females. Mean age of the subjects was 32.9±8.37 years. The number of married and unmarried subjects were similar in the two groups (79 versus 71). Majority of the subjects were staying with the family (69%) and few were staying alone (31%). 10 were ayahs, 21 ward boys, 14 interns, 59 post graduates, 46 staff nurses were included. 11 subjects gave history of substance abuse in the past (7%). 7 subjects had suffered from psychiatric illness (5%) in the past 4 more had family history of psychiatric illness and the mean score for stress recorded was 17.77±6.4, which was indicative of mild stress. The mean anxiety score was 16.25±6.61 which corresponded to severe anxiety. Conclusions: In this study of healthcare workers, working in fever clinic, triage, wards and ICUs for patients with COVID-19, subjects reported experiencing stress and anxiety, especially ayahs, staff nurses and mainly female healthcare workers directly engaged in diagnosis, treatment, and care for patients with COVID-19.